Firm Size, Institutional Ownership, and Profitability: Determinants of Income Smoothing Practices in Indonesian Manufacturing Firms - Ni Putu Liana Pratiwi; Gerianta Wirawan Yasa (E-Jurnal Akuntansi, 2025)
Income smoothing represents a form of earnings management wherein managers intentionally moderate fluctuations in reported income across periods. This practice typically involves reallocating earnings from periods of higher profitability to those with lower reported income, thereby presenting a more stable earnings trajectory over time. The present study examines the extent to which firm size, institutional ownership, and profitability influence the likelihood of income smoothing. Empirical analysis was conducted on manufacturing firms within the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2017–2019 period. A purposive sampling approach was adopted, resulting in a final sample of 37 firms, yielding 111 firm-year observations. Data were obtained through nonparticipant observation and analysed using logistic regression to evaluate the relationship between the selected variables and the incidence of income smoothing. The results indicate that firm size, institutional ownership, and profitability are each positively associated with the likelihood of income smoothing. These findings provide empirical support for theoretical propositions concerning the incentives behind earnings management practices. Moreover, the study contributes to the broader discourse on corporate financial reporting behaviour in emerging markets and offers insights for regulators, investors, and other stakeholders seeking to understand the determinants of income smoothing practices.